Recent Developments of Flexible CdTe Solar Cells on Metallic Substrates: Issues and Prospects - M. M. Aliyu; M. A. Islam; N. R. Hamzah; M. R. Karim; M. A. Matin; K. Sopian; N. Amin (International Journal of Photoenergy)
This study investigates the key issues in the fabrication of CdTe solar cells on metallic substrates, their trends, and characteristics as well as effects on solar cell performance. Previous research works are reviewed while the successes, potentials, and problems of such technology are highlighted. Flexible solar cells offer several advantages in terms of production, cost, and application over glass-based types. Of all the metals studied as substrates for CdTe solar cells, molybdenum appears the most favorable candidate, while close spaced sublimation (CSS), electrodeposition (ED), magnetic sputtering (MS), and high vacuum thermal evaporation (HVE) have been found to be most common deposition technologies used for CdTe on metal foils. The advantages of these techniques include large grain size (CSS), ease of constituent control (ED), high material incorporation (MS), and low temperature process (MS, HVE, ED). These invert-structured thin film CdTe solar cells, like their superstrate counterparts, suffer from problems of poor ohmic contact at the back electrode. Thus similar strategies are applied to minimize this problem. Despite the challenges faced by flexible structures, efficiencies of up to 13.8% and 7.8% have been achieved in superstrate and substrate cell, respectively. Based on these analyses, new strategies have been proposed for obtaining cheaper, more efficient, and viable flexible CdTe solar cells of the future.